Daily field checking list by Walter Rosene, March 28, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, March 28, 1937. Also notes there were several types of food in the Great Horned Owl nest. Plustek--flatbed